Occurrence and distribution of Armillaria gallica genets in a declining oak stand of southern Italy - de Gioia, T.; Ubaldo, R.; Sicoli, G.; Luisi, N. (Phytopathologia Mediterranea, 2003)
Outbreaks of Armillaria root rot in conifer plantations and declining oak stands are frequently due to the spread of the fungus in the soil over long periods. This paper examines the occurrence and distribution of Armillaria genets in a declining mixed oak stand of southern Italy. Samples of rhizomorphs, mycelial mats and fruit bodies of Armillaria were collected from the soil, stumps, and living and dead trees. A total of 111 Armillaria isolates were collected, all belonging to the species A. gallica. They were grouped in 28 genets by somatic incompatibility. The largest genet covered an area of about 2.6 ha with a linear extent of 300 m. On the basis of an estimated 0.5 m annual growth in the soil, its age was assumed to be about 3 centuries. The results confirm the ability of A. gallica to remain alive and stable in a large area over a long time.